PANDANGAN AL-QUR’AN TERHADAP FEMINISME DAN GENDER : KAJIAN TAFSIR MAUDHU’I - Kusuma, Melinda; Aufa, Muhamad Hanif Al; Nashrulloh Usman, Muhammad Ali (Melati Institute, 2023)
Abstract This article discusses gender feminism in Islam, issues related to feminism and gender are presented in this paper. It is important to have adequate knowledge of feminism and gender, because there are several influences that gave birth to the feminist movement due to a lack of knowledge that in fact Islam has positioned men and women in the best way possible. This article aims to find out how studies in Islam view feminism and gender, by presenting verses of the Qur'an as a reference that equality in Islam does not mean the same, therefore there is a need for further discourse to correct this wrong thinking. The method used in this research is descriptive qualitative and maudhu'i method. This study explains the beginning of the emergence of feminist views until the emergence of the feminist movement which emphasizes women's desire to get equality and the same rights as men. The data used as a reference in this study are in the form or books, books, and scientific papers. The results of this research show that in Islam, the advantages and disadvantages of a man and a woman are well structured, each has rights and obligations, with those differences that should complement each other, because after all what God sees is only piety.